Verbalization vs visualization: the issues of interaction and communication - Levintov, Aleksandr (Archives of Business Research, 2021)
the article contrasts two technologies of distant education and scientific activity: visual (presentations) and verbal (by correspondence, Newtonian). The advantages and disadvantages of both technologies are considered, and a preference is given to writing aimed at thinking.